(untitled) (Research, Society and Development, 2024)
Introduction: Alzheimer’s is a significant challenge for healthcare systems, due to the increasing global aging population, which requires a comprehensive and patient-centered approach. Objective: The research has the general objective of analyzing nursing care for patients with Alzheimer’s in primary care, and the specific objectives of contextualizing Alzheimer’s disease and its characteristics; describe the pathophysiology, diagnosis and treatment of Alzheimer’s Disease; present the importance of the role of nursing professionals and what interventions are carried out. Methodology: This study is a systematic and integrative literature review, the search was carried out virtually from September 2023 to April 2014, in the databases: Scientific Electronic Library Online (Scielo), PUBMED (National Library of Medicine), Latin American and Caribbean Literature in Health Sciences (LILACS) and BDENF. Results: The 15 articles selected for results and discussion addressed the contextualization and characteristics of Alzheimer’s disease, described the pathophysiology, diagnosis and treatment and concluded by integrating nursing into primary care, in addition to realizing the importance of patient-family monitoring. nursing. Conclusion: During primary care, nursing collaboration is crucial to providing holistic, personalized care to individuals and families affected by this debilitating condition. Recognizing the importance of early diagnosis, education and continuous monitoring, it is clear that nurses play a central role in the comprehensive approach to Alzheimer’s, standing out as agents of change and support amidst the growing challenges faced by this increasingly growing population. vulnerable.